Imaging in CNS Drug Discovery and Development Implications for Disease and Therapy - Borsook, David; Beccera, Lino R.; Bullmore, Edward; Hargreaves, Richard J. (Springer New York : Imprint: Springer, 2009)
Imaging is a key area of translational research that provides a unique bridge from the laboratory to the clinic as the same techniques and technologies can applied across the various phases of drug development. Neuroimaging is now central to research and drug development in the neurosciences since it can be used to detect the pharmacological and physiological consequences of drug action within the living brain. Today neuroimaging is used primarily as a biomarker to help optimize our decision-making processes. Neuroimaging tools and technologies can be used to select drug candidates, confirm they engage their targets, link occupancy to biology and then, in a translational fashion, be used to help design the best clinical studies that truly test therapeutic hypotheses. Topics covered include: The role of imaging in drug development Imaging approaches including structural, functional, molecular and chemical imaging Imaging drug action including neuroreceptor mapping to examine drug occupancy characteristics, the involvement of specific neurotransmitter systems in CNS diseases and mechanisms of action Functional mapping to provide pharmacodynamic evidence of central activity, "CNS fingerprinting" of the neuroanatomy of drug effects and disease drug interactions Imaging disease states in preclinical and clinical domains Neuroimaging today is all about the need to identify the best molecules, doses and hypotheses to advance into later stage long term extensive clinical trials that can often be confounded by high placebo response rates. Better decision making in early development allows resources to be focused on the drug candidates and therapeutic hypotheses that have the highest probability of success so that we can bring medical advances to patients as quickly as possible. Imaging in CNS Drug Discovery and Development was written by a group of preeminent international experts in the field of imaging.